Impact of Drug Exposure on Resistance Selection Following Artemether‐Lumefantrine Treatment for Malaria in Children With and Without HIV in Uganda. Issue 3 (14th November 2022) - Kay, Katherine; Goodwin, Justin; Ehrlich, Hanna; Ou, Joyce; Freeman, Tracey; Wang, Kaicheng; Li, Fangyong; Wade, Martina; French, Jonathan; Huang, Liusheng; Aweeka, Francesca; Mwebaza, Norah; et al.
Abstract : Artemisinin‐based combination therapies (ACTs) are the primary treatment for malaria. It is essential to characterize the pharmacokinetics (PKs) and pharmacodynamics (PDs) of ACTs in vulnerable populations at risk of suboptimal dosing. We developed a population PK/PD model using data from our previous study of artemether‐lumefantrine in HIV‐uninfected and HIV‐infected children living in a high‐transmission region of Uganda. HIV‐infected children were on efavirenz‐, nevirapine‐, or lopinavir‐ritonavir‐based antiretroviral regimens, with daily trimethoprim‐sulfamethoxazole prophylaxis. We assessed selection for resistance in two key parasite transporters, pfcrt and pfmdr1, over 42‐day follow‐up and incorporated genotyping into a time‐to‐event model to ascertain how resistance genotype in relation to drug exposure impacts recurrence risk. Two hundred seventy‐seven children contributed 364 episodes to the model (186 HIV‐uninfected and 178 HIV‐infected), with recurrent microscopy‐detectable parasitemia detected in 176 episodes by day 42. The final model was a two‐compartment model with first‐order absorption and an estimated age effect on bioavailability. Systemic lumefantrine exposure was highest with lopinavir‐ritonavir, lowest with efavirenz, and equivalent with nevirapine and HIV‐uninfected children. HIV status and lumefantrine concentration were significant factors associated with recurrence risk. Significant selection was demonstrated for pfmdr1 N86 and pfcrt K76 in recurrent infections, with no evidence of selection for pfmdr1 Y184F. Less sensitive parasites were able to tolerate lumefantrine concentrations ~ 3.5‐fold higher than more sensitive parasites. This is the first population PK model of lumefantrine in HIV‐infected children and demonstrates selection for reduced lumefantrine susceptibility, a concern as we confront the threat to ACTs posed by emerging artemisinin resistance in Africa.